Patient-reported outcomes and experiences assessment in women with breast cancer: portuguese case study - Coelho, Anabela (2023)
© 2023 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).